Pengembangan Wisata Dan Ekonomi Kreatif Lampung Dalam Perspektif Collaborative Governance - Pindo Riski Saputra; Intan Destrilia; Fitri Wahyuni; I Wayan Lendra (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2022)
Good development in the tourism sector is not only seen from the level of acceleration of economic growth in an area such as an increase in the level of economic contribution to PAD (Regional Original Income). Tourism development and the creative economy, if managed optimally and responsibly, will ensure progress in other growth-enhancing sectors such as increasing awareness about the importance of natural and cultural preservation in society, and opening up employment opportunities so that in this case it will affect the community welfare index. The writing method in this research is a qualitative method using a descriptive approach. This descriptive approach describes an empirical phenomenon and fact, by presenting data on Collaborative Governance in the development of the tourism sector in the province of Lampung. The results of the succession to the process of sustainable development on aspects of tourism and the creative economy. Where the sector will contribute to improving the welfare of society. In the concept of Collaborative Governance, the development of tourist destinations and the creative economy, becomes part of a sustainable development plan, because with continuous collaboration and synergy between stakeholders (businessmen, government, academics, the community and the media